Climate Regimes, El Niño-Southern Oscillation, and Meningococcal Meningitis Epidemics - Oluwole, Olusegun Steven Ayodele (Frontiers in Public Health, 2015)
Meningoccocal meningitis is a major public health problem that kills thousands annually in Africa, Europe, North and South America. Occurrence is, however, highest during the dry seasons in Sahel Africa. Interannual changes in precipitation correlate with interannual changes in El Nino-Southern Oscillation (ENSO), while interdecadal changes in precipita- tion correlate with Pacific Decadal Oscillation (PDO). The objective of the study was to determine if there is spectral coherence of seasonal, interannual, and interdecadal changes in occurrence of meningococcal meninigitis in Sahel, Central, and East Africa with interan- nual and interdecadal changes of PDO and ENSO. Time series were fitted to occurrence of meningocococcal meningitis in Sahel, Central, and East Africa, to indices of precipitation anomalies in the Sahel, and to indices of ENSO and PDO anomalies. Morlet wavelet was used to transform the time series to frequency-time domain. Wavelet spectra and coherence analyses were performed. Occurrence of meningococcal meningitis showed seasonal, inter- annual, and interdecadal changes. The magnitude of occurrence was higher during warm climate regime, and strong El Ni nos. Spectra coherence of interannual and interdecadal changes of ENSO and PDO with occurrence of meningococcal meningitis in Sahel, Central, and East Africa were significant at p < 0.0001. Precipitation in Sahel was low during warm climate regimes. Spectra coherence of changes in precipitation in Sahel with ENSO was significant at p < 0.0001. ENSO and PDO are determinants of the seasonal, interannual, and interdecadal changes in occurrence of meningococcocal meningitis. Public health man- agement of epidemics of meningococcal meningitis should include forecast models of changes in ENSO to predict periods of low precipitation, which initiate occurrence.